Analisis Kedip Tegangan Pada Trafo Distribusi 20 KV Fakultas Teknik Universitas Riau Menggunakan Power Quality Analyzer (PQA) - Riko Simalango; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The voltage dip is a disturbance that often occurs in electrical power systems that reduce power quality. In general the voltage dip appear from the use of electrical equipment and electrical machines that consume a lot of power, and will be effect the performance of electronic and sensitive equipments caused by voltage dip. Voltage dip measurement in a 20kV distribution transformer of Engineering Faculty Riau University will be compared with IEEE 1159-1995 Standard. The method use in this research is a direct measurement using Power Quality Analyzer (PQA) KEW 6310 for each phase of the transformer. From the results of measurements from October 21 - October 28, 2019 phase R on Monday, October 21, 2019 At 15:05 WIB voltage dip occurred for 0,2 seconds, the voltage drop was 24,4 volts (10,16%), phase S on Thursday, October 24, 2019 at 15:48 WIB, there was a voltage dip of 25,1 volts (25,1%) for 0,2 second, voltage dip in measurements that have been made a long time the dip category momentary, and phase T are not experiencing a voltage dip, the voltage drop was 10,8 volts (4,50%). Keywords: voltage dip, distribution transformer, power quality analyzer (pqa)